2013
DOI: 10.1155/2013/570859
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Effect of Various Polyols on the Native and the Denatured States of Glucoamylase

Abstract: Different spectral probes were employed to study the stabilizing effect of various polyols, such as, ethylene glycol (EG), glycerol (GLY), glucose (GLC) and trehalose (TRE) on the native (N), the acid-denatured (AD) and the thermal-denatured (TD) states of Aspergillus niger glucoamylase (GA). Polyols induced both secondary and tertiary structural changes in the AD state of enzyme as reflected from altered circular dichroism (CD), tryptophan (Trp), and 1-anilinonaphthalene-8-sulfonic acid (ANS) fluorescence cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
(51 reference statements)
2
11
0
Order By: Relevance
“…The addition of GL (15%) and EG (35%) cause blue shift (from 337 to 332 nm), ( Fig. 2B-C) suggesting the arrangement of Trp residue towards the more hydrophobic environment and this data is compatible with reported study [41].…”
Section: Tryptophan Fluorescence Measurementssupporting
confidence: 91%
“…The addition of GL (15%) and EG (35%) cause blue shift (from 337 to 332 nm), ( Fig. 2B-C) suggesting the arrangement of Trp residue towards the more hydrophobic environment and this data is compatible with reported study [41].…”
Section: Tryptophan Fluorescence Measurementssupporting
confidence: 91%
“…It found that two short chain alkanols (methanol and ethanol) were not effective in inducing significant α-helical structure in acid denatured ficin (ADF). Halogenols had higher influence in inducing the α-helical structure in ADF compared to alkanols [25]. …”
Section: Resultsmentioning
confidence: 99%
“…Evaluations were performed using UV-absorption, fluorescence and circular dichroism spectroscopy, as described earlier in ficin experiments [22,25,31,32] in 10 mM sodium phosphate buffers pH 7.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations